Effects of the Glucose on Belousov-Zhabotinskii System - Hu, Gang; Wang, Wei; Chen, Pan-Pan; Song, Ji-Mei; Qiu, Ling-Guang; Lu, Chuan-Hua; Hu, Lin (Asian Journal of Chemistry, 2010)
This paper reported the effects of glucose on a novel Belousov-Zhabotinskii (B-Z) system (BrO3–-[CuL](ClO4)2-malic acid-H2SO4 system, where L = 5,7,7,12,14,14-hexemethyl- 1,4,8,11-tetraazacyclotetradeca-4,11-diene). Experimental results showed that, by the addition of different amount of glucose to the oscillating system, the change of the oscillation amplitude is linearly proportional to the glucose concentration in the range of 2.5 × 10-3- 2.5 × 10-2 M (r = -0.99523). The addition of glucose also caused the change of oscillation period in the same concentration range. The influences of the concentration of the components on the change of the oscillation amplitude, as well as their influences on the change of oscillation period, have been studied in detail. A tentative mechanism to explain the effects of glucose on the oscillation was proposed.